Synthesis and investigation of photophysicochemical properties of novel ketone-substituted gallium (III) and indium (III) phthalocyanines with high singlet oxygen yield for photodynamic therapy - Gunsel, Armagan; Guzel, Emre; Bilgicli, Ahmet T.; Atmaca, Goknur Yasa; Erdogmus, Ali; Yarasir, M. Nilufer (ELSEVIER, 2017)
This work reports on the synthesis and characterization of phthalocyanines (M = Ga(III) and In(III)) which is peripherally tetra-substituted with 4-(4-hydroxyphenyebutan-2-one and also with 1-(4-hydroxyphenyl)propan1-one. Confirmation of the synthesized phthalocyanine structures performed with a combination of elemental analysis, FTIR, H-1 NMR, C-13 NMR, UV-vis and MALDI-MS spectral data. Also, investigated and discussed the effects of peripherally tetra-substitution with different ketones which contain reactive carbonyl groups on the photochemical (Singlet oxygen quantum yields and photodegradation quantum yields) and photophysical properties (Fluorescence quantum yields and fluorescence behavior) which is very important for biological cell studies on PDT. The singlet oxygen quantum yields give an indication of the efficiency of potential photo sensitizers in photodynamic therapy (PDT). That's why the high results (Phi(Lambda), 0.90, 0.88, 0.60 and 0.80 in DMSO) of spectral measurements showed that all of the complexes can have potential to be used as sensitizers.
Keywords: Phthalocyanine; Gallium and indium; Photochemistry; Photophysic; Ketone; ZINC PHTHALOCYANINES; COMPLEXES; BEHAVIOR; CHLORO; ALPHA; Optics